Reshaping Sacred Spaces into Everyday Living: A Morphological and Graph-Based Analysis of Urban Ancestral Temples in Chinese Historic Districts - Ziyu Liu; Yipin Xu; Yinghao Zhao; Yue Zhao (Buildings)
Analyzing how urban ritual spaces transform into everyday living environments is crucial for understanding the spatial structure of contemporary historical districts, particularly in the context of ancestral temples. However, existing research often neglects the integration of both building-level and block-level perspectives when examining such spatial transitions. Grounded in urban morphological principles, we identify the fundamental spatial units of ancestral temples and their surrounding blocks across the early 20th century and the post-1970s era. Using the topological characteristics of an access structure, we construct corresponding network graphs. We then employ embeddedness and conductance metrics to quantify each temple’s changing position within the broader block structure. Moreover, we apply community detection to uncover the structural evolution of clusters in blocks over time. Our findings reveal that, as institutional and cultural factors drive spatial change, ancestral temples exhibit decreased internal cohesion and increased external connectivity. At the block scale, changes in community structure demonstrate how neighborhood clusters transition from a limited number of building-based clusters to everyday living-oriented spatial clusters. These insights highlight the interplay between everyday life demands, land–housing policies, and inherited cultural norms, offering a comprehensive perspective on the secularization of sacred architecture. The framework proposed here not only deepens our understanding of the spatial transformation process but also provides valuable insights for sustainable urban renewal and heritage preservation.